Software development for estimating the direction of arrival of multipath signal using lab Windows CVI / Faiz Faisal - Faisal, Faiz (1997)
Propagating signals contains a lot of information about the sources that produces them. Not only does each signals' waveform express the nature of the source, its temporal and spatial characteristics combined with the law of physics allows us to determine the source's location. Ho wever, it is array signal processing that will do the process of obtaining the insight of the wave structure. The practical problem of interest in array signal processing are extracting the desired parameter such as direction of arrival (DOA). Beamforming algorithm is integrated into the latest version of the C-language, CVI, where it will be used as a tooi in achieving the DOA of multipath radio signals.